2009
DOI: 10.1210/jc.2009-0960
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glucose Disposal Rate in Assessment of the Metabolic Syndrome and Microvascular Complications in Patients with Type 1 Diabetes

Abstract: Insulin resistance is common in type 1 diabetes patients and is associated with microvascular complications. eGDR, as an insulin resistance marker, provides more useful information than other classical variables such as insulin requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 26 publications
3
68
0
Order By: Relevance
“…Visceral obesity was an independent predictor of CAC progression in a study with older adults without known heart disease (19). Recently eGDR, as an insulin resistance marker, provided more useful information than other classical variables such as insulin requirements, to predict vascular complications in a cohort of T1D individuals (13). In our sample, eGDR was a better predictor of the presence of CAC than the presence of MetS.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Visceral obesity was an independent predictor of CAC progression in a study with older adults without known heart disease (19). Recently eGDR, as an insulin resistance marker, provided more useful information than other classical variables such as insulin requirements, to predict vascular complications in a cohort of T1D individuals (13). In our sample, eGDR was a better predictor of the presence of CAC than the presence of MetS.…”
Section: Discussionmentioning
confidence: 57%
“…Insulin resistance in T1D subjects increases progressively with disease duration and its prevalence in these patients is 12 to 42% (8)(9)(10)(11). Moreover, insulin resistance has been associated with micro-and macrovascular complications in individuals with T1D (11)(12)(13). Although prospective data for the power of CAC to predict coronary heart disease events in T1D subjects are still lacking, measurement of CAC could help in deciding about preventive therapy in this group of patients.…”
mentioning
confidence: 99%
“…However, in recent years the rising prevalence of overweight and obesity in patients with T1D has been highlighted, reaching over 50% in some studies [15], and has been particularly associated with a higher percentage of metabolic syndrome [16] and microvascular complications [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from clinical trials also suggests that the incidence or development of diabetic complications is more likely to depend on the intensity of oxidative stress than on the level of glycemic control (Monnier et al, 1999. Besides, evidence indicates that the degree of insulin resistance correlates with the onset of diabetic complications, independently of glycemic levels (Chillaron et al, 2009). In type 2 diabetic patients, it was reported that gliclazide treatment delayed the progression of diabetic nephropathy only, whereas it produced no significant effect on the development or progression of retinopathy or macrovascular complications (Patel et al, 2008).…”
Section: Does Reduced or Intensive Therapy Of Hyperglycemia Prevent Dmentioning
confidence: 99%